Aspect Ratio Consideration in the Optimisation of Maintenance Downtime for Handling Equipment in a Container Terminal: doi: 10.14456/mijet.2022.18 - Oke, Sunday Ayoola; Adekoya, Abdulganiyu Adegboyega (Engineering Access, 2022)
The idea of downtime optimisation is an effective means of minimizing losses of handling equipment in the container port terminal. Unfortunately, previous research relies on the direct factors of downtime, namely downtime parameter (DTM), probability density function (PDF), cumulative density function (CDF) but fails to use the aspect ratios of parameters to more effectively control downtime using the Taguchi method. This gap has resulted in the wrong results and decision making. To correct this problem, this article proposes six aspect ratio parameters to replace existing parameters, namely DTM/PDF, DTM/CDF, PDF/CDF, PDF/DTM, CDF/DTM, and CDF/PDF. These factors were used to obtain the signal-to-noise ratios, the response table and the optimal parametric settings for each Weibull distribution function parameter of β=0.5, 1 and 3. It was found that the outcome at β=3 had the best values and should be used for decision making. For instance, at β=1, DTM/PDF of 92.56 hrs <DTM/PDF of 1222.33 hrs at β=3 <DTM/PDF of 1706.50 hrs at β=0.5. Consequently, the optimal parametric setting at β=1 is DTM/PDF1 DTM/CDF1 PDF/DTM5 CDF/DTM4 PDF/CDF3 CDF/PDF2. This is interpreted as 92.52 hrs of DTM/PDF, 24.87 hrs of DTM/CDF, 0.0063 hr-1 of PDF/DTM, 0.267 hr-1 of CDF/DTM, 0.2897 hr-1 of CDF/DTM, 0.2897 of PDF/CDF and 3.68 of CDF/PDF. The novelty of this article is the use of aspect ratios of the parameter to effect maintenance optimisation. The presented approach aids the ports engineer in the proper planning and control of ports activities.